2018
DOI: 10.1109/tcbb.2018.2858755
|View full text |Cite
|
Sign up to set email alerts
|

“Super Gene Set” Causal Relationship Discovery from Functional Genomics Data

Abstract: We present a computational framework to identify "causal relationships" among super gene sets. For "causal relationships", we refer to both stimulatory and inhibitory regulatory relationships, regardless of through direct or indirect mechanisms. For super gene sets, we refer to "pathways, annotated lists, and gene signatures", or PAGs. To identify causal relationships among PAGs, we extend the previous work on identifying PAG-to-PAG regulatory relationships by further requiring them to be significantly enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Next, we tested the association between the DS pathway and other pathways enriched in MS based on the expression data. This reveals a regulatory relationship regardless of direct or indirect interactions between pathways [28]. We found quite a few pathways correlated with the DS pathway in either grey or white matter (Fig.…”
Section: Transcriptome Analysis Of Dopaminergic Gene Setsmentioning
confidence: 54%
See 1 more Smart Citation
“…Next, we tested the association between the DS pathway and other pathways enriched in MS based on the expression data. This reveals a regulatory relationship regardless of direct or indirect interactions between pathways [28]. We found quite a few pathways correlated with the DS pathway in either grey or white matter (Fig.…”
Section: Transcriptome Analysis Of Dopaminergic Gene Setsmentioning
confidence: 54%
“…To calculate the relationship between two gene sets, "Super Gene Set" causal relationship analysis was performed as previously described [28]. Gene expression values were discretized as follows: the highest 1/3 absolute gene expression was converted to +1, the lowest 1/3 absolute expression values were represented as -1, while the other 1/3 in between were assigned to 0.…”
Section: Gene Set Causal Relationship Analysismentioning
confidence: 99%
“…We found that cell adhesion pathways are enriched following administration of the dopamine Though evidence suggests that to some extent the levels of dopamine in platelets and urine is associated with symptoms of ASD (Launay et al 1987) (Clin 1992), and also that dopaminergic signaling has been shown to be associated with a wide range of developmental disorders, few studies have described the role of dopamine in producing developmental defects in ASD patients. We conducted causal relationship analysis of several key gene sets for dopaminergic signal transduction with the developmental gene sets of interest (Yue et al 2018). The results indicate that the dopamine gene set is strongly linked to the developmental gene set.…”
Section: Discussionmentioning
confidence: 99%
“…"Super Gene Set" causal relationship analysis was conducted to determine the relationship between two selected gene sets (Yue et al 2018). Gene expression values were discretized: the highest 1/3, lowest 1/3, and the middle 1/3 were assigned to 1, -1, and 0, respectively.…”
Section: Gene Set Causal Relationship Analysismentioning
confidence: 99%
“…The fifth paper, "'Super gene set' casual relationship discovery from functional genomics data", by Zongliang Yue, Michael T. Neylon, Thanh Nguyen, Timothy Ratliff, and Jake J. Chen [5], presents a powerful framework to identify stimulatory and inhibitory regulatory relationships among super gene sets, including pathways, annotated lists, and gene signatures (PAG). They extend their previous work on identifying PAG-to-PAG relationships by further requiring them to be significantly enriched with gene-to-gene coexpression pairs across the two PAGs involved.…”
mentioning
confidence: 99%